HALLAZGO DE ADESMIA BIJUGA PHIL. (FABACEAE) EN LA ZONA COSTERA, REGION DEL MAULE, CHILE CENTRAL - Hahn, Steffen; Gómez, Persy (Gayana Botánica, 2008)
This article reports the rediscovery of the specie Adesmia bijuga Phil. (Fabaceae), in the coastal zone of the Maule Region (35°29’31” S - 72°22’47” W) in central Chile. The population was found between two Pinus radiata D.Don plantations and species of the sclerophyllous shrub. Its state of conservation is unknown.